Chronic dermatophytosis: A clinical, epidemiological, mycological study - Abdullah Mancy (Our Dermatology Online, 2022)
Background: Dermatophytes are a common cause of superficial fungal infection of the skin. The emergence of epidemic-like attacks of those chronic and recurring represents a public health problem. Materials and Methods: Two hundred patients with suspected fungal infection of the skin attending the Dermatology and Venereology Department of Al-Ramadi Teaching Hospital were examined. Fifty-nine patients with chronic dermatophytosis were selected for the study and fifty of those were subjected for culture. History taking and a physical examination were conducted for all patients. A wet mount of 10% potassium hydroxide and culture on Sabouraud dextrose agar was done for selected cases. Results: Among 59 patients with chronic infections, the main age group affected was 29 years old, with a nearly equal sex ratio. The mean duration of the illness was 1.2 years. Tinea corporis was the most common type. The Trichophyton genera were the most common (65%), and Trichophyton mentagrophyte was the most common species isolated (46%). Conclusion: Multiple factors have been associated with the appearance of epidemic-like attacks of chronic dermatophyte infections in Iraq in the last several years. Herein, we would like to shed light on these factors and the pathogens responsible.